1994
DOI: 10.1161/01.str.25.1.86
|View full text |Cite
|
Sign up to set email alerts
|

What causes false clinical prediction of small deep infarcts?

Abstract: Background and Purpose Our goal was to identify factors that play a role in false clinical diagnosis of small deep infarcts.Methods In 350 prospectively registered patients with a first supratentorial ischemic stroke, we clinically differentiated between lacunar and nonlacunar syndromes. Using computed tomography (CT), we distinguished small deep and territorial infarcts and also recorded leukoaraiosis and asymptomatic infarcts. Degree of initial handicap, potential source of cardioembolic stroke, and hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
3
26
1
Order By: Relevance
“…The likelihood that a lacunar stroke might be erroneously diagnosed as a territorial infarct increases in the presence of one or more silent small deep infarcts, as we discussed elsewhere. 53 As have others, we found increasing age strongly related to the presence of silent brain infarcts, mainly due to age dependency of the silent small deep lesions. Thus, with increasing age, hypertensive patients may be at increased risk for silent small deep infarcts probably due to hypertension-related small-vessel lipohyalinosis.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The likelihood that a lacunar stroke might be erroneously diagnosed as a territorial infarct increases in the presence of one or more silent small deep infarcts, as we discussed elsewhere. 53 As have others, we found increasing age strongly related to the presence of silent brain infarcts, mainly due to age dependency of the silent small deep lesions. Thus, with increasing age, hypertensive patients may be at increased risk for silent small deep infarcts probably due to hypertension-related small-vessel lipohyalinosis.…”
supporting
confidence: 77%
“…Also, some patients with a lacunar syndrome but without a visible compatible lesion on CT may have an infarct in the brain stem; we recently discussed CT-negative cases that resemble those with visible symptomatic lacunar infarctions. 53 We found that the presumed lacunar index strokes with a cortical syndrome resembled the lacunar strokes. The likelihood that a lacunar stroke might be erroneously diagnosed as a territorial infarct increases in the presence of one or more silent small deep infarcts, as we discussed elsewhere.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…15 mm in diameter and likely attributable to occlusion of a single perforating artery, whilst large infarcts are considered to result from embolism or intrinsic middle cerebral artery (MCA) disease [1,2,[5][6][7] . In addition to the size of deep infarcts, lacunar syndromes are reported to have important clinical value in predicting lacunar mechanisms of stroke [4,[8][9][10] .…”
mentioning
confidence: 99%
“…The other "classic" lacunar syndromes were variably associated with larger lesions. 33 The usefulness of clinical lacunar syndromes to predict small, deep cerebral infarcts was evaluated 34 and found to be quite accurate (88%), using all 4 classic lacunar syndromes (pure motor stroke, pure sensory stroke, sensorimotor stroke, and AH). Ataxic hemiparesis was the most accurate of the 4 syndromes, with a predictive ability of 100%.…”
Section: Gorman Et Al December 1998mentioning
confidence: 99%